Biorefinery Approach Applied to the Production of Food Colourants and Biostimulants from Oscillatoria sp - Morillas-España, Ainoa; Bermejo, Ruperto; Abdala-Díaz, Roberto Teófilo; Ruiz, Ángela; Lafarga, Tomás; Acién-Fernández, Francisco Gabriel; Fernández-Sevilla, José María (IOAP-MPDI, 2022)
In this study, a biorefinery based on Oscillatoria sp. is developed to produce high-value compounds such as C-phycocyanin, used in food colourant applications, and biostimulants, used in agriculture-related applications. First, the Oscillatoria biomass production was optimized at a pilot scale in an open raceway reactor, with biomass productivities equivalent to 52 t/ha·year being achieved using regular fertilizers as the nutrient source. The biomass produced contained 0.5% C-phycocyanins, 95% of which were obtained after freeze–thawing and extraction at pH 6.5 and ionic strength (FI) 100 mM, with a purity ratio of 0.71 achieved in the final extract. This purity ratio allows for use of the extract directly as a food colourant. Then, the extract’s colourant capacity on different beverages was evaluated. The results confirm that C-phycocyanin concentrations ranging from 22 to 106 mg/L produce colours similar to commercial products, thus avoiding the need for synthetic colourants. The colour remained stable for up to 12 days. Moreover, the safety of the extracted C-phycocyanin was confirmed through toxicity tests. The waste biomass was evaluated for use as a biostimulant, with the results confirming a relevant auxin-like positive effect. Finally, an economic analysis was conducted to evaluate different scenarios. The results confirm that the production of both C-phycocyanin and biostimulants is the best scenario from an economic standpoint. Therefore, the developed biomass processing scheme provides an opportunity to expand the range of commercial applications for microalgae-related processes.
Keywords: Microalgas; Biorefinery; Phycocyanin; Biostimulants; Microalgae; Toxicity; Bioeconomy